2014
DOI: 10.1370/afm.1688
|View full text |Cite
|
Sign up to set email alerts
|

The 5 R's: An Emerging Bold Standard for Conducting Relevant Research in a Changing World

Abstract: Research often fails to find its way into practice or policy in a timely way, if at all. Given the current pressure and pace of health care change, many authors have recommended different approaches to make health care research more relevant and rapid. An emerging standard for research, the "5 R's" is a synthesis of recommendations for care delivery research that (1) is relevant to stakeholders; (2) is rapid and recursive in application; (3) redefines rigor; (4) reports on resources required; and (5) is replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 50 publications
(46 reference statements)
0
76
0
Order By: Relevance
“…For ALED, health educators had difficulty, from the standpoint of both their own schedule and participants' schedules, to plan for 12 consecutive weeks of program delivery during the trial's time of year. Other barriers of practical concern for translational research are concerns with costs [8,54]. Covering the costs of program materials and staff travel to implementation sites impeded adoption.…”
Section: Discussionmentioning
confidence: 99%
“…For ALED, health educators had difficulty, from the standpoint of both their own schedule and participants' schedules, to plan for 12 consecutive weeks of program delivery during the trial's time of year. Other barriers of practical concern for translational research are concerns with costs [8,54]. Covering the costs of program materials and staff travel to implementation sites impeded adoption.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a changing paradigm for health care research, such as the 5R perspective or the framework of critical realism, 3 will be needed for this work. The 5R perspective [36][37][38] advocates that intervention-based health care research should (1) be relevant to stakeholders, (2) be rapid and recursive, (3) redefine rigor while maintaining scientific integrity, (4) report on required resources needed to implement interventions, and (5) be replicable. 28 Critical realism, 3 which is compatible with the 5R perspective, [36][37][38] prioritizes empirical observation with the goal of finding regularities from those observations that can be generalized.…”
Section: Very Little Ipecp Research Has Dealt With Big Picture Healthmentioning
confidence: 99%
“…Processes from grant funding, ethics approval, recruitment, submission, and publication could be streamlined, if the obstacles were identified and the importance of their removal acknowledged. 2,28 Involving clinicians and patients in research The appropriateness of research questions can be improved by increasing clinician and patient participation in the process of priority setting, at all levels from national funding bodies to local departments. For example, since 2008 the UK Arthritis Research Campaign has had a nationally agreed strategic plan for intervention research in the major musculoskeletal disorders that is based upon priorities identified by healthcare professionals and patients.…”
Section: Increasing the Value Of Clinical Researchmentioning
confidence: 99%